Pressure effect on phonon frequencies in some transition metals: A molecular dynamics study - Kazanc, S; Ozgen, S (Elsevier, 2005)
It is important to determine the atomic lattice vibrations of metallic materials, under high-pressure conditions, due to its effects on material properties such as thermal, electrical and optical conductions. In this work, we have investigated the changes of acoustic phonon frequencies with hydrostatic pressure for Cu, Ni, Al, Ag and An transition metals, using molecular dynamics (MD) simulations based on embedded atom method (EAM). For this aim, we have adopted the embedded atom potential proposed by Sutton and Chen. The phonon frequencies have been calculated from the dynamical matrix for [100], [110] and [111] high symmetry directions of the Brillouin zone. The obtained results show that the hydrostatic pressure causes an increment in phonon frequencies, and this rising do not depend linearly on the increasing pressure. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: molecular dynamics simulation; embedded atom method; phonon frequency; dynamical matrix